Nanocarbon and polyaniline composite Schiff base anti-explosion coating and preparation method thereof
By using Schiff base explosion-resistant elastomers combined with nanocarbon and polyaniline in the coating materials of offshore wind power equipment, the problem of poor flame retardant performance of existing coating materials is solved, and a more efficient and lasting flame retardant effect is achieved.
Patent Information
- Application Number
- CN202411959910.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
AI Technical Summary
The existing polyurea anti-explosion elastomer coating materials have poor flame retardant performance, which is difficult to meet the requirements of offshore wind power equipment for flame retardant and explosion resistance.
The Schiff base explosion-resistant elastomer composited with nanocarbon and polyaniline is used as a reactive flame retardant. Through chemical reaction with the end amino polyether, the flame retardant is introduced into the molecular chain of the polymer elastomer material to achieve intrinsic flame retardant.
The flame retardant ability of the coating material is improved, making the flame retardant elements connected in the polymer network in chemical bonds, making it difficult to migrate and exudate, and the flame retardant performance is more efficient and lasting.
Smart Images

Figure CN119736005A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field related to explosion-proof materials, and in particular to a Schiff base explosion-proof coating composited with nano-carbon and polyaniline and a preparation method thereof. Background Art
[0002] In the marine industry, offshore wind power has a bright future. In the process of developing and utilizing offshore wind power, many technical problems different from those of onshore wind power will be encountered. Offshore wind turbines must withstand marine environments such as high humidity, high salt fog, and long sunshine. In addition, they are also affected by high temperatures and strong winds in different seasons. If corrosion protection treatment is not carried out, the corrosion of offshore wind power equipment will be very serious. In addition, equipment and facilities such as offshore booster stations and energy storage battery cabins also need to meet fire and explosion protection requirements.
[0003] The offshore booster station platform carries transformers, geospatial information systems (GIS) and other supporting electrical equipment. As the "heart" of offshore wind power, it converges the current delivered by the wind turbine generators in the wind farm, and plays an important role in power transmission and transfer for the entire wind farm. The flame retardant and explosion-proof performance of the offshore booster station platform has an important impact on the reliable operation of the offshore booster station.
[0004] Foreign studies have shown that the cost of maintaining offshore wind power systems at sea is 50 times the manufacturing cost. Therefore, it is imperative to adopt reliable and effective new technologies to provide long-term corrosion, flame retardancy, explosion resistance and safety protection for offshore wind power systems.
[0005] Polyurea explosion-proof elastomer coating materials are widely used due to their good flexibility, high strength, fast curing speed, insensitivity to ambient temperature and humidity, and the ability to achieve thick coatings in one application. However, the coating is composed of a semi-prepolymer generated by the reaction of isocyanate and terminal hydroxyl polyether, terminal amino polyether, and amine curing agent. As a polymer material, it is easy to catch fire and emit a large amount of toxic gas. Therefore, the research and development of flame-retardant explosion-proof elastomer coating materials is particularly important for the flame retardancy and explosion resistance of offshore booster station platforms. Summary of the invention
[0006] The present application provides a nano-carbon and polyaniline composite Schiff base anti-explosion coating and a preparation method thereof, so as to solve the problem of poor flame retardancy of polyurea anti-explosion elastomer coating materials existing in the prior art.
[0007] In the first aspect, the present application provides a nanocarbon and polyaniline composite Schiff base anti-explosion coating comprising a component A and a component B which are independently packaged, wherein the component A comprises a terminal hydroxyl polyether and isocyanate MDI-50 in a mass ratio of 1:8~20, and the component B comprises an amino-terminated polyether in a mass ratio of 40~80:10~20:15~25, a nanocarbon and polyaniline composite Schiff base anti-explosion elastomer, and a chain extender, wherein the nanocarbon and polyaniline composite Schiff base anti-explosion elastomer is a Schiff base anti-explosion elastomer formed by a composite of a nanocarbon material and a secondary doped polyaniline-Schiff base compound, and the nanocarbon material comprises at least one of graphene and carbon nanotubes.
[0008] Optionally, the nanocarbon and polyaniline composite Schiff base anti-explosion elastomer is prepared by combining nanocarbon material and aniline in a mass ratio of 1:5-25 in a 4-formylbenzoic acid solution with ammonium persulfate and benzotriazole through primary doping, dedoping and secondary doping.
[0009] Optionally, the molecular structure of the Schiff base anti-explosion elastomer contains a triazole structure and a carboxylic acid structure.
[0010] Optionally, the nano-carbon and polyaniline composite Schiff base anti-explosion elastomer contains a secondary doped polyaniline-Schiff base compound modified with nano-carbon material.
[0011] Optionally, the NCO mass fraction of component A is 18%, and the isocyanate index of component A is 1-1.2.
[0012] Optionally, the B component also includes titanium dioxide pigment and kaolin filler, and the molecular weight of the amino-terminated polyether is 1000-8000.
[0013] In a second aspect, the present application provides a method for preparing the above-mentioned nano-carbon and polyaniline composite Schiff base anti-explosion coating, wherein the nano-carbon and polyaniline composite Schiff base anti-explosion coating comprises a component A and a component B that are independently packaged from each other, and the preparation method of the component A comprises: (1) According to the mass ratio of terminal hydroxyl polyether to isocyanate MDI-50 of 1:8-20, the terminal hydroxyl polyether is added into the reactor for dehydration process operation, wherein the temperature is controlled to rise to 105°C within 30 minutes, and then the vacuum system is turned on, and the temperature is continued to rise to 110°C, and the temperature is maintained at 115±3°C, and the vacuum degree is maintained above 0.075MPa, and the vacuum dehydration is carried out for more than 2 hours; (2) closing the vacuum system and opening the vent valve, filling with nitrogen to restore to normal pressure, taking samples and measuring the moisture content, and if the moisture content is still higher than 0.5‰, repeating the dehydration process until the moisture content of the polyether is lower than 0.5‰; when the moisture content of the polyether is lower than 0.5‰, closing the vacuum system and opening the vent valve, filling with nitrogen to restore to normal pressure, cooling to a material temperature of less than 60°C to obtain the dehydrated hydroxyl-terminated polyether; (3) Turn on the agitator and heating device, add isocyanate MDI-50 to the dehydrated hydroxyl-terminated polyether in a mass ratio of 1:8 to 20, control the feeding speed, and add it slowly and evenly within 30 minutes. The feeding should be completed before the material temperature rises to 60°C; (4) After the addition is completed, the temperature is controlled to rise to 75°C within 20 minutes, and the temperature is controlled to be kept at 75±2°C for 2 hours; then the temperature is raised to 82°C within 10 minutes, and the temperature is controlled to be kept at 82±2°C for 2 hours. During the reaction, the material temperature is strictly controlled not to exceed 86°C; (5) After the reaction is completed, stop heating and turn on the cooling device. Control the cooling speed so that the material temperature drops below 60°C within 20 minutes. Continue stirring for 30 minutes. Then filter with a 100-mesh copper mesh and fill. After filling, the packaging barrel must be filled with nitrogen for protection to ensure that the sealing performance of the packaging container is intact, so as to obtain the A component in an independently sealed package.
[0014] Optionally, the preparation method of the B component includes: (1) According to the mass ratio of the Schiff base anti-explosion elastomer composited with terminal amino polyether, nanocarbon and polyaniline and the chain extender of 40-80:10-20:15-25, the Schiff base anti-explosion elastomer composited with terminal amino polyether, nanocarbon and polyaniline is first added and mixed, and the chain extender is added after the stirrer and the heating device are turned on. When the temperature is raised to 105°C within 30 minutes, the vacuum system is turned on, and the temperature is continued to rise to 110°C, and the temperature is maintained at 110±3°C, the vacuum degree is maintained above 0.075MPa, and vacuum dehydration is performed for more than 2 hours; (2) Turn off the vacuum system and open the vent valve, fill with nitrogen to restore to normal pressure, take samples and measure the moisture content. If the moisture content is still higher than 0.5‰, repeat the vacuum dehydration operation until the moisture content is lower than 0.5‰; (3) When the moisture content is lower than 0.5‰, the vacuum system is closed and the vent valve is opened. Nitrogen is filled to restore the pressure to normal. Then, the ground pigment titanium dioxide and filler kaolin are added to the reactor and stirred at high speed for 1 hour. (4) Turn on the vacuum system, maintain the vacuum degree at 0.075MPa, keep the temperature at 80±2℃, evacuate and degas for 15min, turn off the vacuum system and heating device, stir at low speed, and then fill with nitrogen to remove the vacuum. Cool to the material temperature <60℃, filter with a 100-mesh copper mesh, and then fill. After filling, the packaging barrel must be filled with nitrogen for protection to ensure that the packaging container is sealed and intact. The B component is independently sealed and packaged.
[0015] Optionally, the nano-carbon and polyaniline composite Schiff base anti-explosion elastomer is prepared by the following method: (1) Prepare 1 mol / L 4-formylbenzoic acid as the doping acid system, take three 20 ml portions of the prepared 1 mol / L 4-formylbenzoic acid solution respectively, wherein the first portion adds aniline and nanocarbon material according to the mass ratio of nanocarbon material to aniline ANI of 1:5-25, the second portion adds ammonium persulfate, and the third portion adds benzotriazole, and the molar ratio of aniline, ammonium persulfate and benzotriazole added is 0.8:1:1. Mix the three solutions under a nitrogen atmosphere, and then evenly mix them at 70°C for 1-2 h, and then place them at room temperature for 24 h. The obtained product is washed with ethanol and deionized water successively until neutral, and after drying and grinding, a functional composite material of nanocarbon material and primary doped polyaniline-Schiff base compound is obtained; (2) adding excess ammonia water to the functional composite material of the nanocarbon material and the primary doped polyaniline-Schiff base compound for dedoping, stirring with a magnetic stirrer for 1 to 2 hours, standing at room temperature for 24 hours, washing the obtained product with ethanol and deionized water until neutral, and finally drying and grinding to obtain a functional composite material of the nanocarbon material and the intrinsic polyaniline-Schiff base compound; (3) The nanocarbon material and the functional composite material of the nanocarbon material and the intrinsic polyaniline-Schiff base compound are added to 1 mol / L 4-formylbenzoic acid in a mass ratio of 1:20, mixed and stirred, and then allowed to stand for 24 h. After filtration, the mixture is washed with ethanol and deionized water in turn until neutral, and finally dried and ground to obtain a nanocarbon and polyaniline composite Schiff base anti-explosion elastomer.
[0016] This application has at least the following beneficial technical effects: The present application provides a nano-carbon and polyaniline composite Schiff base anti-explosion coating and a preparation method thereof. A nano-carbon and polyaniline composite Schiff base anti-explosion elastomer is added to component B as a reactive flame retardant. The chemical reaction between the nano-carbon and polyaniline composite Schiff base anti-explosion elastomer and the amino-terminated polyether in component B is used to introduce the reactive flame retardant into the molecular chain of the polymer elastomer material to achieve intrinsic flame retardancy. The flame retardant elements are connected in the polymer network in the form of chemical bonds, making it difficult for the flame retardant elements to migrate and seep out, and the flame retardant ability is more efficient and durable. Secondly, 4-formylbenzoic acid and benzotriazole are used as raw materials to synthesize a special molecular structure through Schiff base reaction. The N-containing Schiff base structure can undergo self-crosslinking reaction at high temperature, thereby improving the flame retardant properties of the Schiff base-based anti-explosion elastomer composited with nanocarbon and polyaniline; furthermore, the polymerization of the polyaniline nanofiber material is modified by the nanocarbon material to provide a template for the growth of the polymer skeleton to form a dense network structure, and 4-formylbenzoic acid serves as both a reactant of the Schiff base reaction and an acid environment and counter anion for the polymerization reaction of polyaniline; the nanocarbon material and aniline are combined with ammonium persulfate and benzotriazole in a 4-formylbenzoic acid solution through primary doping, dedoping and secondary doping to form a composite, thereby solving the problems of poor compatibility, easy agglomeration and difficult application of reactive flame retardants in matrix materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0018] Figure 1 This is a scanning electron microscope comparative analysis diagram of the different product morphologies provided in the examples of the present application.
[0019] The above drawings have shown clear embodiments of the present application, which will be described in more detail later. These drawings and text descriptions are not intended to limit the scope of the present application in any way, but to illustrate the concept of the present application to those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0021] In order to solve the technical problems existing in the prior art, the present application provides a nano-carbon and polyaniline composite Schiff base anti-explosion coating and a preparation method thereof, wherein a nano-carbon and polyaniline composite Schiff base anti-explosion elastomer is added to component B as a reactive flame retardant, and a chemical reaction between the nano-carbon and polyaniline composite Schiff base anti-explosion elastomer and the amino-terminated polyether in component B is utilized to introduce the reactive flame retardant into the molecular chain of the polymer elastomer material to achieve intrinsic flame retardancy, and the flame retardant elements are connected in the polymer network in the form of chemical bonds, making it difficult for the flame retardant elements to migrate and seep out, and the flame retardant ability is more efficient and durable; secondly, 4-formylbenzoic acid and benzotriazole are used as raw materials, and the reaction of the Schiff base is used to synthesize the The N-containing Schiff base structure has a special molecular structure. The Schiff base structure can undergo self-crosslinking reaction at high temperature, thereby improving the flame retardant properties of the Schiff base-based anti-explosion elastomer composited with nanocarbon and polyaniline; furthermore, the polymerization of the polyaniline nanofiber material is modified by the nanocarbon material to provide a template for the growth of the polymer skeleton to form a dense network structure, and 4-formylbenzoic acid is used as a reactant of the Schiff base reaction and also provides an acid environment and counter anion for the polymerization reaction of polyaniline; the nanocarbon material and aniline are combined with ammonium persulfate and benzotriazole in a 4-formylbenzoic acid solution through primary doping, dedoping and secondary doping to form a composite, thereby solving the problems of poor compatibility, easy agglomeration and difficult application of reactive flame retardants in matrix materials.
[0022] The technical solution of the present application is described in detail below through specific embodiments. It should be noted that the following specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described in detail in some embodiments. Example 1
[0023] The embodiment of the present application provides a nano-carbon and polyaniline composite Schiff base anti-explosion coating, including a component A and a component B that are independently packaged, wherein the component A includes a terminal hydroxyl polyether T-5000 and an isocyanate MDI-50 in a mass ratio of 1:8~20, and the component B includes an amino-terminated polyether T-5000 in a mass ratio of 40~80:10~20:15~25, a nano-carbon and polyaniline composite Schiff base anti-explosion elastomer, and a chain extender, wherein the nano-carbon and polyaniline composite Schiff base anti-explosion elastomer is a Schiff base anti-explosion elastomer formed by a composite of a nano-carbon material and a secondary doped polyaniline-Schiff base compound, and the nano-carbon material includes at least one of graphene and carbon nanotubes.
[0024] The nano-carbon and polyaniline composite Schiff base anti-explosion elastomer used in the embodiment of the present application is prepared by combining nano-carbon material and aniline in a mass ratio of 1: 5 to 25 in a 4-formylbenzoic acid solution with ammonium persulfate and benzotriazole through primary doping, dedoping and secondary doping. The molecular structure of the Schiff base anti-explosion elastomer contains a triazole structure and a carboxylic acid structure. The nano-carbon and polyaniline composite Schiff base anti-explosion elastomer contains a secondary doped polyaniline-Schiff base compound modified by the nano-carbon material.
[0025] The embodiment of the present application provides a nanocarbon and polyaniline composite Schiff base anti-explosion coating, wherein the NCO mass fraction of component A is 18%, and the isocyanate index of component A is 1 to 1.2. Preferably, the isocyanate index of component A is 1.08, NCO refers to the isocyanate group in the chemical material, and the NCO mass fraction refers to the mass of the isocyanate (-NCO) group contained in 100g of the sample. When the NCO mass fraction of component A is 18% and the isocyanate index of component A is 1.08, the flame retardant and anti-explosion effect of component A after mixing with component B is the best.
[0026] Furthermore, the component B of the embodiment of the present application also includes titanium dioxide pigment and kaolin filler, and the molecular weight of the amino-terminated polyether used in the component B is 1000-8000. Example 2
[0027] The present application provides a method for preparing the nano-carbon and polyaniline composite Schiff base anti-explosion coating, wherein the nano-carbon and polyaniline composite Schiff base anti-explosion coating comprises a component A and a component B which are packaged independently from each other, wherein the component A and the component B are mixed in a volume ratio of 1:1 to form a nano-carbon and polyaniline composite Schiff base anti-explosion coating for use. The preparation method of component A comprises: (1) According to the mass ratio of terminal hydroxyl polyether to isocyanate MDI-50 of 1:8-20, the terminal hydroxyl polyether is added into the reactor for dehydration process operation, wherein the temperature is controlled to rise to 105°C within 30 minutes, and then the vacuum system is turned on, and the temperature is continued to rise to 110°C, and the temperature is maintained at 115±3°C, and the vacuum degree is maintained above 0.075MPa, and the vacuum dehydration is carried out for more than 2 hours; (2) closing the vacuum system and opening the vent valve, filling with nitrogen to restore to normal pressure, taking samples and measuring the moisture content, and if the moisture content is still higher than 0.5‰, repeating the dehydration process until the moisture content of the polyether is lower than 0.5‰; when the moisture content of the polyether is lower than 0.5‰, closing the vacuum system and opening the vent valve, filling with nitrogen to restore to normal pressure, cooling to a material temperature of less than 60°C to obtain the dehydrated hydroxyl-terminated polyether; (3) Turn on the agitator and heating device, add isocyanate MDI-50 to the dehydrated hydroxyl-terminated polyether in a mass ratio of 1:8 to 20, control the feeding speed, and add it slowly and evenly within 30 minutes. The feeding should be completed before the material temperature rises to 60°C; (4) After the addition is completed, the temperature is controlled to rise to 75°C within 20 minutes, and the temperature is controlled to be kept at 75±2°C for 2 hours; then the temperature is raised to 82°C within 10 minutes, and the temperature is controlled to be kept at 82±2°C for 2 hours. During the reaction, the material temperature is strictly controlled not to exceed 86°C; (5) After the reaction is completed, stop heating and turn on the cooling device. Control the cooling speed so that the material temperature drops below 60°C within 20 minutes. Continue stirring for 30 minutes. Then filter with a 100-mesh copper mesh and fill. After filling, the packaging barrel must be filled with nitrogen for protection to ensure that the sealing performance of the packaging container is intact, so as to obtain the A component in an independently sealed package.
[0028] In the process of preparing component A, the step-by-step temperature increase and the step-by-step temperature control and insulation are strictly controlled during the reaction process to prevent the isocyanate in component A from accelerating the self-polymerization reaction due to excessively high temperature, avoid excessive consumption of NCO by the reaction, effectively maintain the NCO content in the system, and ensure product performance; at the same time, the step-by-step temperature increase and the step-by-step temperature control and insulation are strictly controlled during the reaction process to effectively prevent the reaction from failing to reach the reaction endpoint for a long time due to too low temperature, avoid a large amount of unreacted hydroxyl and NCO in the system, and effectively ensure the flame retardant and explosion-resistant properties of component A.
[0029] The preparation method of component B comprises: (1) According to the mass ratio of amino-terminated polyether T-5000, nanocarbon and polyaniline composite Schiff base anti-explosion elastomer, and chain extender E-100 of 40~80:10~20:15~25, first add amino-terminated polyether T-5000, nanocarbon and polyaniline composite Schiff base anti-explosion elastomer to mix, turn on the stirrer and heating device, then add the chain extender E-100, control the temperature to 105°C within 30 minutes, turn on the vacuum system, continue to heat to 110°C, maintain the temperature at 110±3°C, maintain the vacuum degree above 0.075MPa, and vacuum dehydrate for more than 2 hours; (2) Turn off the vacuum system and open the vent valve, fill with nitrogen to restore to normal pressure, take samples and measure the moisture content. If the moisture content is still higher than 0.5‰, repeat the vacuum dehydration operation until the moisture content is lower than 0.5‰; (3) When the moisture content is lower than 0.5‰, the vacuum system is closed and the vent valve is opened. Nitrogen is filled to restore the pressure to normal. Then, the ground pigment titanium dioxide and filler kaolin are added to the reactor and stirred at high speed for 1 hour. (4) Turn on the vacuum system, maintain the vacuum degree at 0.075MPa, keep the temperature at 80±2℃, evacuate and degas for 15min, turn off the vacuum system and heating device, stir at low speed, and then fill with nitrogen to remove the vacuum. Cool to the material temperature <60℃, filter with a 100-mesh copper mesh, and then fill. After filling, the packaging barrel must be filled with nitrogen for protection to ensure that the packaging container is sealed and intact. The B component is independently sealed and packaged.
[0030] In the process of preparing component B, the high molecular weight amino polyether is first mixed with the Schiff base anti-explosion elastomer composited with flame retardant nanocarbon and polyaniline, and then the low molecular weight chain extender E-100 (polyether polyamine) is added. This process effectively avoids the problem of reduced amine value caused by the volatilization loss of low molecular weight polyether polyamine, greatly increases the stability of the system and the flame retardant and anti-explosion properties of the components.
[0031] The preparation method of the Schiff base anti-explosion elastomer composited with nano-carbon and polyaniline comprises: (1) Prepare 1 mol / L 4-formylbenzoic acid as the doping acid system, take three 20 ml portions of the prepared 1 mol / L 4-formylbenzoic acid solution respectively, wherein the first portion adds aniline and nanocarbon material according to the mass ratio of nanocarbon material to aniline ANI of 1:5-25, the second portion adds ammonium persulfate, and the third portion adds benzotriazole, and the molar ratio of aniline, ammonium persulfate and benzotriazole added is 0.8:1:1. Mix the three solutions under a nitrogen atmosphere, and then evenly mix them at 70°C for 1-2 h, and then place them at room temperature for 24 h. The obtained product is washed with ethanol and deionized water successively until neutral, and after drying and grinding, a functional composite material of nanocarbon material and primary doped polyaniline-Schiff base compound is obtained; (2) adding excess ammonia water to the functional composite material of the nanocarbon material and the primary doped polyaniline-Schiff base compound for dedoping, stirring with a magnetic stirrer for 1 to 2 hours, standing at room temperature for 24 hours, washing the obtained product with ethanol and deionized water until neutral, and finally drying and grinding to obtain a functional composite material of the nanocarbon material and the intrinsic polyaniline-Schiff base compound; (3) The nanocarbon material and the functional composite material of the nanocarbon material and the intrinsic polyaniline-Schiff base compound are added to 1 mol / L 4-formylbenzoic acid in a mass ratio of 1:20, mixed and stirred, and then allowed to stand for 24 h. After filtration, the mixture is washed with ethanol and deionized water in turn until neutral, and finally dried and ground to obtain a nanocarbon and polyaniline composite Schiff base anti-explosion elastomer.
[0032] The nanocarbon and polyaniline composite Schiff base anti-explosion elastomer provided in the embodiment of the present application can solve the problem that the reactive flame retardant has poor compatibility with the matrix material, easily increases the viscosity of the matrix, and is difficult to apply. On the one hand, the nanocarbon and polyaniline composite Schiff base anti-explosion elastomer provided in the embodiment of the present application uses 4-formylbenzoic acid and benzotriazole as raw materials, and synthesizes the N-containing Schiff base structure with a special molecular structure through the Schiff base reaction. The Schiff base structure can undergo self-crosslinking reaction at high temperature to improve the flame retardant performance; on the other hand, the polymerization of the polyaniline nanofiber material is modified by the nanocarbon material to provide a template for the growth of the polymer skeleton to form a dense network structure. 4-formylbenzoic acid is not only a reactant for the Schiff base reaction, but also provides an acid environment and anions for the polyaniline polymerization reaction. Through the functional composite of nanocarbon materials and polyaniline-Schiff base compounds, the problems of poor compatibility, easy agglomeration, and difficult application of reactive flame retardants in the matrix material are solved.
[0033] refer to Figure 1 As shown, Figure 1 (a) is a scanning electron microscope photo of polyaniline PANI; (b) is a scanning electron microscope photo of carbon nanotubes CNTs; (c) is a scanning electron microscope photo of carbon nanotubes and polyaniline composite Schiff base anti-explosion elastomer CNTs / PANI-FN; (d) is a scanning electron microscope photo of graphene RGO; (e) is a scanning electron microscope photo of graphene and polyaniline composite Schiff base anti-explosion elastomer RGO / PANI-FN. As can be seen from Figure a, a large number of agglomerations occur in the primary doping of polyaniline, forming nanoparticles. Figure b is a multi-walled carbon nanotube with a clustered structure. Figure c corresponds to the functional composite material CNTs / PANI-FN of carbon nanotube / polyaniline-Schiff base compound. It can be clearly seen from the figure that the polyaniline molecular chain has a significant increase, the fiber has good uniformity, and the arrangement is more compact to form a dense network structure. The carbon nanotube plays a good template role in the polymerization process and effectively avoids agglomeration. The N-containing Schiff base structure with a special molecular structure is synthesized through the Schiff base reaction. The Schiff base structure can undergo self-crosslinking reaction at high temperature to improve the flame retardant properties. Example 3
[0034] The present application provides a method for preparing the nano-carbon and polyaniline composite Schiff base anti-explosion coating, wherein the nano-carbon and polyaniline composite Schiff base anti-explosion coating comprises a component A and a component B which are packaged independently from each other, wherein the component A and the component B are mixed in a volume ratio of 1:1 to form a nano-carbon and polyaniline composite Schiff base anti-explosion coating for use. The preparation method of component A comprises: 1. Dehydration process of end-capping materials (1) Check whether the reactor, auxiliary equipment and vacuum system are operating normally; (2) weighing 36 g of hydroxyl-terminated polyether and adding it into a reaction kettle for dehydration process operation; (3) Turn on the agitator (gradually adjust to medium speed, 600 rpm) and the heating device, control the temperature to rise to 105°C within 30 minutes, turn on the vacuum system, continue to heat up to 110°C, maintain the temperature at 115±3°C, maintain the vacuum degree above 0.075MPa, and vacuum dehydrate for more than 2 hours; (4) Turn off the vacuum system and open the vent valve, fill with nitrogen to restore to normal pressure, take samples and measure the moisture content. If the moisture content is still higher than 0.5‰, repeat the dehydration process in (3) until the moisture content of the polyether is lower than 0.5‰; (5) When the moisture content of the polyether is lower than 0.5‰, close the vacuum system and open the vent valve, fill with nitrogen to restore to normal pressure, and cool to a material temperature of <60°C for use.
[0035] 2. Preparation of semi-prepolymer (1) Turn on the agitator and heating device, add 6g of dehydrated hydroxyl-terminated polyether and 60g of isocyanate MDI-50; control the feeding speed and add it slowly and evenly within 30 minutes. The feeding should be completed before the material temperature rises to 60°C; (2) After the addition is completed, the temperature is raised to 75°C within 20 minutes, and the temperature is controlled at 75±2°C for 2 hours; then the temperature is raised to 82°C within 10 minutes, and the temperature is controlled at 82±2°C for 2 hours, and the material temperature is strictly controlled not to exceed 86°C; (3) After the reaction is completed, stop heating and turn on the cooling device. Control the cooling speed to reduce the material temperature to below 60°C within 20 minutes and continue stirring for 30 minutes. (4) Filter with a 100-mesh copper mesh and then fill. After filling, the packaging barrel must be filled with nitrogen to ensure that the packaging container is sealed intact to obtain component A. At the same time, sample and determine the NCO mass fraction of the semi-prepolymer. After testing, the NCO mass fraction of the semi-prepolymer is 18% and the isocyanate index is 1.08.
[0036] The preparation method of component B comprises: (1) Check whether the reactor and its accessories are operating normally; (2) Measure the materials and add them into the reactor for dehydration process operation: First, add 60g of high molecular weight (molecular weight 1000-8000) terminated amino polyether (T-5000) and 15g of Schiff base anti-explosion elastomer composited with nanocarbon and polyaniline, turn on the stirrer (gradually adjusted to medium speed, 600rpm) and the heating device, then add 22g of chain extender E-100, control the temperature to 105℃ within 30min, turn on the vacuum system, continue to heat to 110℃, maintain the temperature at 110±3℃, maintain the vacuum degree above 0.075MPa, and vacuum dehydrate for more than 2h; (3) Close the vacuum system and open the vent valve, fill with nitrogen to restore to normal pressure, take samples and measure the moisture content. If the moisture content is still higher than 0.5‰, repeat the operation of (2) until the moisture content is lower than 0.5‰; (4) After the moisture content is qualified, close the vacuum system and open the vent valve, and fill with nitrogen to restore to normal pressure.
[0037] (5) Add 1.8 g of titanium dioxide pigment and 1.2 g of kaolin filler into the reactor and stir at high speed (1000 rpm) for 1 h; (6) Turn on the vacuum system, maintain the vacuum degree at 0.075 MPa, keep the temperature at 80±2℃, and degas for 15 minutes; (7) Turn off the vacuum system and heating device, stir at low speed, then fill with nitrogen to remove the vacuum, cool to a temperature of less than 60°C, filter with a 100-mesh copper mesh, and then fill. After filling, the packaging barrel must be filled with nitrogen for protection to ensure that the packaging container is sealed intact to obtain component B.
[0038] In the process of preparing component A, the step-by-step temperature increase and step-by-step temperature control and insulation are strictly controlled during the reaction to prevent the isocyanate in component A from accelerating the self-polymerization reaction due to excessively high temperature, avoid excessive consumption of NCO by the reaction, effectively maintain the NCO content in the system, and ensure product performance; at the same time, the step-by-step temperature increase and step-by-step temperature control and insulation are strictly controlled during the reaction to effectively prevent the reaction from failing to reach the reaction endpoint for a long time due to too low temperature, avoid a large amount of unreacted hydroxyl groups and NCO in the system, and effectively ensure the flame retardant and explosion resistance of component A; in the process of preparing component B, the process of first mixing the high molecular weight amino polyether with the Schiff base anti-explosion elastomer composited with flame retardant nanocarbon and polyaniline, and then adding the low molecular weight polyether polyamine is adopted, which effectively avoids the problem of reduced amine value caused by the volatilization loss of the low molecular weight polyether polyamine, greatly increases the stability of the system and the flame retardant and explosion resistance of the product.
[0039] The nanocarbon and polyaniline composite Schiff base anti-explosion elastomer used in Example 3 of the present application is prepared by the following method: (1) Prepare 1 mol / L 4-formylbenzoic acid as the doping acid system. Take three 20 ml portions of 4-formylbenzoic acid solution, add aniline (ANI) and a certain amount of nanocarbon material to one portion, and set the mass ratio of nanocarbon material to aniline ANI to 1:5-1:25; add ammonium persulfate (APS) to one portion, and add benzotriazole (HB) to one portion, and the molar ratio of aniline, ammonium persulfate and benzotriazole is n(ANI):n(APS):n(HB)=0.8:1:1. Mix the three solutions under a nitrogen atmosphere, and then mix them evenly at 70°C for 1-2 h, and let them stand at room temperature for 24 h. The obtained product is washed with ethanol and deionized water to neutrality, and then dried and ground to obtain a functional composite material of nanocarbon material and primary doped polyaniline-Schiff base compound.
[0040] (2) Using the nanocarbon material obtained in (1) and the functional composite material of the once-doped polyaniline-Schiff base compound as raw materials, adding excess ammonia water for dedoping, stirring with a magnetic stirrer for 1-2 h, and standing at room temperature for 24 h, the obtained product is washed with ethanol and deionized water until neutral, and finally dried and ground to obtain the functional composite material of the nanocarbon material and the intrinsic polyaniline-Schiff base compound.
[0041] (3) The nanocarbon material, the nanocarbon material obtained in (2) and the functional composite material of the intrinsic polyaniline-Schiff base compound are added to 1 mol / L 4-formylbenzoic acid in a ratio of 1:20, mixed and stirred, and then allowed to stand for 24 h. After filtration, the mixture is washed with ethanol and deionized water in turn until neutral, and finally dried and ground to obtain the functional composite material of the nanocarbon material and the secondary doped polyaniline-Schiff base compound, that is, the nanocarbon and polyaniline composite Schiff base anti-explosion elastomer is obtained by dry grinding. Example 4
[0042] The present application also provides a method for preparing the nano-carbon and polyaniline composite Schiff base anti-knock elastomer, the method comprising: (1) Prepare 1 mol / L 4-formylbenzoic acid as the doping acid system, take three 20 ml portions of the prepared 1 mol / L 4-formylbenzoic acid solution respectively, wherein the first portion is added with aniline and nanocarbon material according to the mass ratio of nanocarbon material to aniline ANI of 1:5, 1:10, 1:12, 1:18 or 1:25, the second portion is added with ammonium persulfate, and the third portion is added with benzotriazole, and the molar ratio of aniline, ammonium persulfate and benzotriazole added is 0.8:1:1, the three solutions are mixed under a nitrogen atmosphere, and then uniformly mixed at a temperature of 70°C for 1-2 h, and then placed at room temperature for 24 h, the obtained product is washed with ethanol and deionized water successively until neutral, and after drying and grinding, a functional composite material of nanocarbon material and primary doped polyaniline-Schiff base compound is obtained; (2) adding excess ammonia water to the functional composite material of the nanocarbon material and the primary doped polyaniline-Schiff base compound for dedoping, stirring with a magnetic stirrer for 1 to 2 hours, standing at room temperature for 24 hours, washing the obtained product with ethanol and deionized water until neutral, and finally drying and grinding to obtain a functional composite material of the nanocarbon material and the intrinsic polyaniline-Schiff base compound; (3) Add the nanocarbon material and the functional composite material of the nanocarbon material and the intrinsic polyaniline-Schiff base compound to 1 mol / L 4-formylbenzoic acid in a mass ratio of 1:20, stir and mix, let stand for 24 hours, filter and wash with ethanol and deionized water to neutrality, and finally dry and grind to obtain a nanocarbon and polyaniline composite Schiff base anti-explosion elastomer. The nanocarbon material used in the preparation process includes at least one of graphene and carbon nanotubes.
[0043] The flame retardant and anti-explosion mechanism of the nano-carbon and polyaniline composite Schiff base anti-explosion elastomer used in the embodiment of the present application is as follows: The nanocarbon and polyaniline composite Schiff base anti-explosion elastomer material can decompose the non-flammable gases such as NH3 and N2 during combustion, thereby diluting the concentration of combustible gases and O2 in the gas phase. It has co-curing properties during the synthesis of elastomer materials: the functional composite material of nanocarbon material / polyaniline-Schiff base compound, as a reactive flame retardant, can react with amino polyether in anti-explosion flame retardant materials, while improving the flame retardant and mechanical properties of elastomer materials.
[0044] In addition, during the polymerization process of the nanocarbon and polyaniline composite Schiff base anti-explosion elastomer material, the triazole structure and carboxylic acid structure were introduced into the nanocarbon and polyaniline composite Schiff base anti-explosion elastomer composite material through the Schiff base reaction of 4-formylbenzoic acid and benzotriazole. Among them, the introduction of the triazole structure: (1) brings higher curing activity to the reaction system, which is conducive to the formation of a stable cured product and the performance of co-curing characteristics; (2) the triazole structure itself has good flame retardant properties and can decompose at high temperature to generate non-flammable gases such as N2, which plays a diluting role; (3) the triazole structure has good thermal stability. In a high temperature environment, the triazole structure can remain stable and is not easy to decompose, which can improve the thermal stability of the elastomer material; (4) from the perspective of corrosion protection, benzotriazole can react with metal to form an adsorption film, which increases the anodic activation energy of iron and thus reduces the corrosion rate of iron. The carboxylic acid structure can undergo a dehydration reaction at high temperature to promote the dehydration of the matrix material into carbon. The generated carbon layer has high thermal insulation performance. At the same time, this dehydration reaction also helps to consume part of the heat in the combustion process, thereby further improving the flame retardant properties of the elastomer material.
[0045] Therefore, by simultaneously introducing carboxylic acid and triazole structures into the functional composite material of Schiff base anti-explosion elastomer composited with nanocarbon and polyaniline through Schiff base reaction, a functional composite material with co-curing properties can be synthesized, which can simultaneously improve the combustion safety performance and mechanical properties of the elastomer material. Through the intrinsic flame retardant design and co-curing properties, the functional composite material of Schiff base anti-explosion elastomer composited with nanocarbon and polyaniline promotes the formation of the anti-explosion elastomer coating material network, and can be evenly dispersed in the elastomer coating material to form a maze effect. When the coating material is attacked by flames, the self-carbonization promotes the cross-linking and carbonization of the elastomer coating material, and finally forms a dense, continuous porous protective carbon layer. The porous expansion protective carbon layer not only isolates heat, but also forms a maze effect, prolonging the path for the escape of combustible gas and toxic gas to contact the flame, and inhibiting the release of smoke and toxic gas.
[0046] The present application provides a nano-carbon and polyaniline composite Schiff base anti-explosion coating and a preparation method thereof, wherein a nano-carbon and polyaniline composite Schiff base anti-explosion elastomer is added to component B as a reactive flame retardant, and the reactive flame retardant is introduced into the molecular chain of the polymer elastomer material to achieve intrinsic flame retardancy by utilizing the chemical reaction between the nano-carbon and polyaniline composite Schiff base anti-explosion elastomer and the amino-terminated polyether in component B, and the flame retardant elements are connected in the polymer network in the form of chemical bonds, making it difficult for the flame retardant elements to migrate and seep out, and the flame retardant ability is more efficient and durable; compared with the additive flame retardant used in the prior art, the embodiment of the present application uses a reactive flame retardant to enhance the flame retardant effect, which has relatively less negative impact on the mechanical properties of the elastomer material matrix, thereby overcoming the problem of large loss of mechanical properties of the elastomer material and easy migration caused by the introduction of flame retardants. By introducing a Schiff base anti-explosion elastomer composite of nanocarbon and polyaniline and reacting it with component B, a multifunctional elastomer coating material is obtained. The mechanical properties of the elastomer material will not be greatly sacrificed, and may even be improved to a certain extent. It also has the advantages of long-lasting flame retardancy and good thermal stability.
[0047] Reactive flame retardants often have poor compatibility with matrix materials, which easily increases the viscosity of the matrix and is difficult to apply. The embodiment of the present application adopts two methods of organic combination to solve this problem. First, 4-formylbenzoic acid and benzotriazole are used as raw materials, and a Schiff base structure containing N with a special molecular structure is synthesized by Schiff base reaction. The Schiff base structure can undergo self-crosslinking reaction at high temperature to improve the flame retardant properties of Schiff base anti-explosion elastomers composited with nanocarbon and polyaniline; furthermore, the polymerization of polyaniline nanofiber materials is modified by nanocarbon materials to provide a template for the growth of polymer skeletons to form a dense network structure. 4-formylbenzoic acid is not only a reactant for Schiff base reaction, but also provides an acid environment and anions for polyaniline polymerization reaction; nanocarbon materials and aniline are combined with ammonium persulfate and benzotriazole in 4-formylbenzoic acid solution through primary doping, dedoping and secondary doping, which solves the problems of poor compatibility, easy agglomeration and difficult application of reactive flame retardants in matrix materials.
[0048] Analysis of flame retardant effect: The example sample of the present application (coating material with Schiff base anti-explosion elastomer composited with nano-carbon and polyaniline), comparative sample 1 (simple polyurea elastomer coating material) and comparative sample 2 (elastomer coating with carbon nanotube / polyaniline functional material) were placed in the same flame combustion environment and deflagration environment for testing at the same time, and the observation and recording results were as follows: Comparative sample 1: combustion started at 13 minutes, the flame tip height was greater than 150 mm, internal combustion dripping appeared, and combustion was complete at 8 minutes; Comparative sample 2: combustion occurred at 16 minutes, the flame tip height was greater than 150 mm, internal combustion dripping appeared, and combustion was complete at 9 minutes; The sample of the embodiment of the present application: no combustion occurred within 60 minutes, and no large amount of smoke and toxic gas was released; It shows that compared with comparative sample 1 (pure polyurea elastomer coating material) and comparative sample 2 (elastomer coating with added carbon nanotube / polyaniline functional material), the nano-carbon and polyaniline composite Schiff base anti-explosion coating sample of the embodiment of the present application has significant flame retardant and anti-explosion effects.
[0049] Analysis of mechanical property maintenance effect: According to GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" and GB / T 529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled and crescent-shaped specimens)", relevant mechanical property tests were carried out, and the results are as follows: Comparative sample 1: tensile strength 23.62MPa, tear strength 118.8N / mm, elongation at break 207.6%; Comparative sample 2: tensile strength 23.75MPa, tear strength 120.2N / mm, elongation at break 208.3%; The sample of the embodiment of the present application: tensile strength 23.82MPa, tear strength 119.5N / mm, elongation at break 210.7%; It shows that, compared with comparative sample 1 (pure polyurea elastomer coating material) and comparative sample 2 (elastomer coating with added carbon nanotube / polyaniline functional material), the tensile strength, tear strength, and elongation at break of the Schiff base anti-explosion coating sample of the nanocarbon and polyaniline composite of the present application embodiment of the present invention are not reduced, and the mechanical strength of the original material is still maintained; It should be understood that the present application is not limited to the precise structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.
Claims
1. A nanocarbon and polyaniline composite Schiff base anti-explosion coating, characterized in that: The nano-carbon and polyaniline composite Schiff base anti-explosion coating comprises a component A and a component B which are packaged independently of each other, wherein the component A comprises a terminal hydroxyl polyether and isocyanate MDI-50 in a mass ratio of 1:8-20, and the component B comprises an amino-terminated polyether in a mass ratio of 40-80:10-20:15-25, a nano-carbon and polyaniline composite Schiff base anti-explosion elastomer, and a chain extender, wherein the nano-carbon and polyaniline composite Schiff base anti-explosion elastomer is a Schiff base anti-explosion elastomer formed by a composite of a nano-carbon material and a secondary doped polyaniline-Schiff base compound, and the nano-carbon material comprises at least one of graphene and carbon nanotubes.
2. The nanocarbon and polyaniline composite Schiff base anti-explosion coating according to claim 1, characterized in that: The nano-carbon and polyaniline composite Schiff base anti-explosion elastomer is prepared by combining nano-carbon material and aniline in a mass ratio of 1:5-25 in a 4-formylbenzoic acid solution with ammonium persulfate and benzotriazole through primary doping, dedoping and secondary doping.
3. The nanocarbon and polyaniline composite Schiff base anti-explosion coating according to claim 1, characterized in that: The molecular structure of the Schiff base anti-explosion elastomer contains a triazole structure and a carboxylic acid structure.
4. The nanocarbon and polyaniline composite Schiff base anti-explosion coating according to claim 1, characterized in that: The nano-carbon and polyaniline composite Schiff base anti-explosion elastomer contains a secondary doped polyaniline-Schiff base compound modified by nano-carbon materials.
5. The nanocarbon and polyaniline composite Schiff base anti-explosion coating according to claim 1, characterized in that: The NCO mass fraction of the A component is 18%, and the isocyanate index of the A component is 1-1.
2.
6. The nanocarbon and polyaniline composite Schiff base anti-explosion coating according to claim 1, characterized in that: The B component also includes pigment titanium dioxide and filler kaolin, and the molecular weight of the amino-terminated polyether is 1000-8000.
7. A method for preparing the nano-carbon and polyaniline composite Schiff base anti-explosion coating according to any one of claims 1 to 5, wherein the nano-carbon and polyaniline composite Schiff base anti-explosion coating comprises a component A and a component B that are packaged independently of each other, characterized in that: The preparation method of the A component comprises: (1) According to the mass ratio of terminal hydroxyl polyether to isocyanate MDI-50 of 1:8-20, the terminal hydroxyl polyether is added into the reactor for dehydration process operation, wherein the temperature is controlled to rise to 105°C within 30 minutes, and then the vacuum system is turned on, and the temperature is continued to rise to 110°C, and the temperature is maintained at 115±3°C, and the vacuum degree is maintained above 0.075MPa, and the vacuum dehydration is carried out for more than 2 hours; (2) closing the vacuum system and opening the vent valve, filling with nitrogen to restore to normal pressure, taking samples and measuring the moisture content, and if the moisture content is still higher than 0.5‰, repeating the dehydration process until the moisture content of the polyether is lower than 0.5‰; when the moisture content of the polyether is lower than 0.5‰, closing the vacuum system and opening the vent valve, filling with nitrogen to restore to normal pressure, cooling to a material temperature of less than 60°C to obtain the dehydrated hydroxyl-terminated polyether; (3) Turn on the agitator and heating device, add isocyanate MDI-50 to the dehydrated hydroxyl-terminated polyether in a mass ratio of 1:8 to 20, control the feeding speed, and add it slowly and evenly within 30 minutes. The feeding should be completed before the material temperature rises to 60°C; (4) After the addition is completed, the temperature is controlled to rise to 75°C within 20 minutes, and the temperature is controlled to be kept at 75±2°C for 2 hours; then the temperature is raised to 82°C within 10 minutes, and the temperature is controlled to be kept at 82±2°C for 2 hours. During the reaction, the material temperature is strictly controlled not to exceed 86°C; (5) After the reaction is completed, stop heating and turn on the cooling device. Control the cooling speed so that the material temperature drops below 60°C within 20 minutes. Continue stirring for 30 minutes. Then filter with a 100-mesh copper mesh and fill. After filling, the packaging barrel must be filled with nitrogen for protection to ensure that the sealing performance of the packaging container is intact, so as to obtain the A component in an independently sealed package.
8. The method according to claim 7, characterized in that The preparation method of the B component comprises: (1) According to the mass ratio of the Schiff base anti-explosion elastomer composited with terminal amino polyether, nanocarbon and polyaniline and the chain extender of 40-80:10-20:15-25, the Schiff base anti-explosion elastomer composited with terminal amino polyether, nanocarbon and polyaniline is first added and mixed, and the chain extender is added after the stirrer and the heating device are turned on. When the temperature is raised to 105°C within 30 minutes, the vacuum system is turned on, and the temperature is continued to rise to 110°C, and the temperature is maintained at 110±3°C, the vacuum degree is maintained above 0.075MPa, and vacuum dehydration is performed for more than 2 hours; (2) Turn off the vacuum system and open the vent valve, fill with nitrogen to restore to normal pressure, take samples and measure the moisture content. If the moisture content is still higher than 0.5‰, repeat the vacuum dehydration operation until the moisture content is lower than 0.5‰; (3) When the moisture content is lower than 0.5‰, the vacuum system is closed and the vent valve is opened. Nitrogen is filled to restore the pressure to normal. Then, the ground pigment titanium dioxide and filler kaolin are added to the reactor and stirred at high speed for 1 hour. (4) Turn on the vacuum system, maintain the vacuum degree at 0.075MPa, keep the temperature at 80±2℃, evacuate and degas for 15min, turn off the vacuum system and heating device, stir at low speed, and then fill with nitrogen to remove the vacuum. Cool to the material temperature <60℃, filter with a 100-mesh copper mesh, and then fill. After filling, the packaging barrel must be filled with nitrogen for protection to ensure that the packaging container is sealed and intact. The B component is independently sealed and packaged.
9. The method according to claim 8, characterized in that The nano-carbon and polyaniline composite Schiff base anti-explosion elastomer is prepared by the following method: (1) Prepare 1 mol / L 4-formylbenzoic acid as the doping acid system, take three 20 ml portions of the prepared 1 mol / L 4-formylbenzoic acid solution respectively, wherein the first portion adds aniline and nanocarbon material according to the mass ratio of nanocarbon material to aniline ANI of 1:5-25, the second portion adds ammonium persulfate, and the third portion adds benzotriazole, and the molar ratio of aniline, ammonium persulfate and benzotriazole added is 0.8:1:
1. Mix the three solutions under a nitrogen atmosphere, and then evenly mix them at 70°C for 1-2 h, and then place them at room temperature for 24 h. The obtained product is washed with ethanol and deionized water successively until neutral, and after drying and grinding, a functional composite material of nanocarbon material and primary doped polyaniline-Schiff base compound is obtained; (2) adding excess ammonia water to the functional composite material of the nanocarbon material and the primary doped polyaniline-Schiff base compound for dedoping, stirring with a magnetic stirrer for 1 to 2 hours, standing at room temperature for 24 hours, washing the obtained product with ethanol and deionized water until neutral, and finally drying and grinding to obtain a functional composite material of the nanocarbon material and the intrinsic polyaniline-Schiff base compound; (3) The nanocarbon material and the functional composite material of the nanocarbon material and the intrinsic polyaniline-Schiff base compound are added to 1 mol / L 4-formylbenzoic acid in a mass ratio of 1:20, mixed and stirred, and then allowed to stand for 24 h. After filtration, the mixture is washed with ethanol and deionized water in turn until neutral, and finally dried and ground to obtain a nanocarbon and polyaniline composite Schiff base anti-explosion elastomer.